DEVELOPING WRITING ASSESSMENT TASK OF ANALYTICAL EXPOSITION TEXT BASED ON CURRICULUM 2013 FOR ELEVENTH GRADE STUDENTS OF SMK TELKOM MEDAN - Yulita Sarwinna; Rahmad Husein; Anggarini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aims to develop English writing assessment tasks of analytical exposition text for eleventh grade students of multimedia program at SMK Telkom Medan. This study was conducted by research and development (R & D) design through six phases; gathering information and data, analyzing data, designing new writing assessment tasks, validating by experts, revising writing assessment tasks, and final product. The subject of this research was the eleventh grade students of multimedia program at SMK Telkom Medan. The instruments for collecting data were questionnaire and interview. The data were gathered by administering interview to the English teacher and distributing questionnaire to the eleventh grade students of multimedia program to get the students’ needs. The evaluators of the developed writing assessments were two experts namely an English lecturer and English teacher. The developed assessment in each task was authentic assessment that consists of three competences, such as, attitude competence, knowledge competence, and skill competence. The writing assessment tasks have been validated by experts. The average score are 3.6 based on the highest interval of numerical scale which was 4.00. In the form percentage, it got 91.3% so it was categorized “Very Good”. It means the developing English writing assessments are appropriate for the eleventh grade students of multimedia program at SMK Telkom Medan.  Keywords: Research and Development (R&D), Writing, Assessment Task, Analytical Exposition Text.